1991
DOI: 10.1111/j.1464-5491.1991.tb01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Control May Influence the Increased Superoxide Generation in Diabetic Serum

Abstract: Superoxide anion (O2-) generation in serum from 10 Type 1 diabetic patients and 10 normal subjects was measured ex vivo. The amount of O2- production was significantly increased in diabetic serum 0.41 +/- 0.04 (+/- SD) vs 0.14 +/- 0.04 mumol l-1 min-1, p less than 0.001) and correlated with fasting plasma glucose and glycosylated protein levels in both diabetic (r = 0.72, p less than 0.01, and r = 0.62, p less than 0.05) and normal r = 0.75, p less than 0.01 and r = 0.64, p less than 0.05) subjects. Improved m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 12 publications
6
53
0
1
Order By: Relevance
“…In providing support for possible increased rates of glucose autoxidation and the subsequent generation of free radicals, the diabetic group in this study showed higher blood glucose levels, thus providing more substrate for autoxidation purposes. In addition, it has been suggested that poor metabolic control may influence the generation of O 2 · − radicals in diabetic serum [3]. This is partially supported our data demonstrating a higher HbA 1c level in the diabetic group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In providing support for possible increased rates of glucose autoxidation and the subsequent generation of free radicals, the diabetic group in this study showed higher blood glucose levels, thus providing more substrate for autoxidation purposes. In addition, it has been suggested that poor metabolic control may influence the generation of O 2 · − radicals in diabetic serum [3]. This is partially supported our data demonstrating a higher HbA 1c level in the diabetic group.…”
Section: Discussionsupporting
confidence: 90%
“…Reports suggest that patients with diabetes mellitus are susceptible to increased levels of oxidative stress [1,2], although it is not known whether the increase in reactive oxygen species (ROS) is a causative factor or merely an epiphenomenon. Poor intravascular substrate control is largely regarded as a factor contributing to the increase in superoxide anions (O 2 · − ) that has previously been observed in diabetic serum [3]. Other potential mechanisms relating to enhanced oxidative stress in diabetes include a compromised antioxidant defence system, glucose autoxidation, the formation of advanced glycated end-products and a change in the glutathione redox status [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Amadori albumin can be associated with diabetic nephropathy, and it can be localised in retinal capillaries from diabetic patients [38]. Furthermore, all these studies are also consistent with the idea that oxidative stress observed in patients or diabetic animals is directly related to the metabolic control of the disease [33,34,35,36,37,38,46,47,48].…”
Section: Discussionsupporting
confidence: 71%
“…Ceriello and cols. (17) were able to demonstrate a significant increase in the production of superoxide anions (SOA) in 10 patients with T1DM, although the study was limited to adult subjects. On the other hand, Hsu and cols.…”
Section: Discussionmentioning
confidence: 98%